2021
DOI: 10.1016/j.heliyon.2021.e07360
|View full text |Cite
|
Sign up to set email alerts
|

Mixed phytochemicals mediated synthesis of copper nanoparticles for anticancer and larvicidal applications

Abstract: The synthesis of copper nanoparticles (CuNPs) using Wrightia tinctoria (Wt) R.Br extract is defined in this article as being convenient, environmentally friendly, and non-toxic. UV-visible spectrophotometry, FT-IR, XRD, particle size analyser, SEM-EDAX and TEM methods were used to describe the physicochemical properties of Wt extract mediated synthesized CuNPs (Wt-CuNPs). The Wt-CuNPs synthesized was found to be monodispersed and spherical, with an average size of 15 nm. Gas chromatography and mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 56 publications
2
18
0
1
Order By: Relevance
“…Previous articles on the oxidation of different Cu NPs have reported that those studies are incomplete, and learning about the initial oxidation and oxidation progress through time in different environmental conditions is needed [37]. The value of this knowledge is to learn the oxidation degree of the Cu NPs after storage and to know the role of the coating in the chemical stability [38][39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous articles on the oxidation of different Cu NPs have reported that those studies are incomplete, and learning about the initial oxidation and oxidation progress through time in different environmental conditions is needed [37]. The value of this knowledge is to learn the oxidation degree of the Cu NPs after storage and to know the role of the coating in the chemical stability [38][39].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ahamed et al [ 103 ] found that copper ferrite (CuFe 2 O 4 ) nanoparticles (NPs) added to the culture of human breast cancer MCF-7 cells can cause intracellular oxidation stress response, exerting anti-cancer effects, specifically manifested in the production of ROS and the consumption of glutathione (GSH) ( Figure 3 ). Furthermore, Rajagopal et al [ 104 ] found that copper nanoparticles (Wt-CuNPs) have obvious cytotoxic effects on MCF-7 cells. The specific mechanism is mainly due to the release of copper ions from the nanoparticles and the binding of copper ions to tumor cell DNA, causing DNA damage and the resulting apoptotic cell death.…”
Section: Clinical Application Of Copper-based Nanoparticles In Oncologymentioning
confidence: 99%
“…Later, enough Na + and Cl − counter ions were introduced to keep the salt concentration in the complex system at 0.15 M. From the NPT (Isothermal-Isobaric, constant number of particles, pressure, and temperature) equilibration, each complex was assigned a simulation time of 50 ns for the final run. Using the internet server "WebGRO" for macromolecular simulations (https://simlab.uams.edu/), the root mean square deviation (RMSD), root mean square fluctuation (RMSF), radiation of gyration (RGY), and SASA (solvent accessible surface area) of the trajectory analysis were executed in the GROMACS simulation program [47].…”
Section: Molecular Dynamics (Md) Simulation Studiesmentioning
confidence: 99%